Hydrocarbon Signatures of the Ectoparasitoid Sphecophaga vesparum Shows Wasp Host Dependency - Cintia Akemi Oi (Insects, 2020)
Sphecophaga vesparum often parasitizes nests of vespid wasps such as Vespula vulgaris and Vespula germanica. Inside the colonies, the ectoparasitic larvae feed on the immature forms of the wasps. There are two adult forms of S. vesparum. The large, winged adults emerge from either rigid yellow cocoons or the orange cocoons used for overwintering. The small, brachypterous females emerge from soft, white cocoons. The species is facultative deuterotokous, producing mostly parthenogenic females and infrequently producing males. Here, we describe the production of chemical compounds related to the different developmental forms of the parasitoid S. vesparum (larvae, pupae and adults). We also compare the chemical profiles of the parasitoid wasp adults to those of their two main host species, Vespula vulgaris and Vespula germanica. The results show differences in hydrocarbon composition of larvae, pupae and adults of S. vesparum. Our results also suggest a partial mimicry of each of the two host species, mostly relating to linear alkanes present in both parasitoids and the host vespid wasp species. This matching is likely due to the recycling of the prey’s hydrocarbons, as has been found in other species of parasitoids.